Advanced Heart Failure Treatment Modalities and Hospice Care: The Need for High Level Care Coordination. (September 2019) - Burnside, Lee; Whyte, Sharon; Cooper, Stephanie G.
Advanced heart failure therapies such as ventricular assist devices and home inotrope use are becoming more common. Technology advances as well as increased indications for use of such therapies is leading to a higher percentage of patients with end-stage heart failure receiving these therapies at end of life. We present a case of a young man with dilated cardiomyopathy who undergoes advanced cardiac care in the setting of progressively declining cardiac function. Our case outlines the importance of acute care, palliative care, and hospice services being coordinated prior to and during acute-care services to provide goal-concordant and expeditious care. With advancing medical therapies for heart disease, increased coordination and collaboration of services are needed, particularly between hospice and acute-care services.